2017
DOI: 10.1016/j.chom.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Defective HIV-1 Proviruses Are Expressed and Can Be Recognized by Cytotoxic T Lymphocytes, which Shape the Proviral Landscape

Abstract: SUMMARY Despite antiretroviral therapy, HIV-1 persists in memory CD4+ T cells creating a barrier to cure. The majority of HIV-1 proviruses are defective and considered clinically irrelevant. Using cells from HIV-1-infected individuals and reconstructed patient-derived defective proviruses, we show that defective proviruses can be transcribed into RNAs that are spliced and translated. Proviruses with defective major splice donors (MSDs) can activate novel splice sites to produce HIV-1 transcripts and cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
372
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 317 publications
(390 citation statements)
references
References 71 publications
18
372
0
Order By: Relevance
“…We observed a significant decrease in levels of HIV DNA in the anti-CD3/CD28 plus HIV-specific CD8 + T cell clones (Figure proviruses, resulting in selection for proviruses with epitope deletions. These data are in line with previous reports that provide indirect evidence implicating CD8 + T cells in shaping the defective proviral landscape in vivo (29). Thus, we conclude that, under conditions of ex vivo latency reversal, HIV-specific CD8 + T cells can eliminate a subset of defective HIV proviruses, while intactinducible reservoirs resist CD8 + T cell-mediated killing.…”
Section: T Cells and Again Did Not Observe Reductions In Intact-inducsupporting
confidence: 82%
See 4 more Smart Citations
“…We observed a significant decrease in levels of HIV DNA in the anti-CD3/CD28 plus HIV-specific CD8 + T cell clones (Figure proviruses, resulting in selection for proviruses with epitope deletions. These data are in line with previous reports that provide indirect evidence implicating CD8 + T cells in shaping the defective proviral landscape in vivo (29). Thus, we conclude that, under conditions of ex vivo latency reversal, HIV-specific CD8 + T cells can eliminate a subset of defective HIV proviruses, while intactinducible reservoirs resist CD8 + T cell-mediated killing.…”
Section: T Cells and Again Did Not Observe Reductions In Intact-inducsupporting
confidence: 82%
“…Of note, we have recently demonstrated that a subset of defective proviruses is able to express viral antigens, resulting in recognition by HIV-specific CD8 + T cells (29). The magnitudes of the CD8 + T cell plus LRA-mediated reductions in HIV DNA observed in the current study, along with the lack of decreases in intact-inducible proviruses as measured by QVOA, were highly suggestive of preferential elimination of cells harboring defective proviruses.…”
Section: Hiv-specific Cd8 + T Cell Elimination Of Defective Provirusesupporting
confidence: 48%
See 3 more Smart Citations